Simple Soft-Information Developers Based on Parallel Detection Scheme in Bit-Patterned Media Recording (BPMR) Systems - Mutita Mattayakan; Siwakon Sokjabok; Chanon Warisam (2021 36th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2021)
Among the alternate ultra-high density data storage technologies, bit-patterned media recording (BPMR) is one of the mentioned technologies that was proposed to achieve a higher density. Due to the closeness between the magnetic islands, so the readback sequences are disrupted from the effect of two-dimensional (2D) interference, which includes both intersymbol interference (ISI) and intertrack interference (ITI). In this paper; therefore, we propose the simple and effective soft-information developers (SIDs) to improve the soft-information that are obtained from both vertical and horizontal detectors. An optimal weight was optimized under the BPMR channel before multiplying with the horizontal soft-information. The proposed SIDs and conventional 2D detector's performances were carefully compared in the terms of BER. The results show that our proposed methods achieve a gain of approximately 8 dB at a BER of 10 -3 .
Keywords: Magnetic properties of thin films; Advanced Data Storage Technologies; Phase-change materials and chalcogenides